2020
DOI: 10.3139/120.111542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the welding parameters on the surface morphology of resistance spot welded AISI 304 stainless steel joints

Abstract: Resistance spot welding is an extensively used production process in the industry. The joint strength of sheet metal parts bonded by resistance spot welding is expected to be sufficient. Furthermore, it is desirable that the appearance of the welding area be acceptable on visible surfaces. In regard to having an adequate surface appearance on the welded area, is necessary to remove the color changes on the unpainted surfaces and to eliminate the indentations caused by the welding pressure. In this study, an ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Velmurugan et al [8] investigated the lowtemperature diffusion bonding of Ti6Al4V alloy and duplex stainless steel (DSS) and found that the tensile shear strength decreases with an increase in bonding temperature. Eroglu et al [9] investigated the diffusion bonding of Ti6Al4V alloy and Micro-DSS using Cu as an interlayer.…”
Section: Introductionmentioning
confidence: 99%
“…Velmurugan et al [8] investigated the lowtemperature diffusion bonding of Ti6Al4V alloy and duplex stainless steel (DSS) and found that the tensile shear strength decreases with an increase in bonding temperature. Eroglu et al [9] investigated the diffusion bonding of Ti6Al4V alloy and Micro-DSS using Cu as an interlayer.…”
Section: Introductionmentioning
confidence: 99%
“…Onal and Kaya [21] optimized RSW paraemters using Taguchi method for joining Al-Si coated 22MnB5 sheets. Cavdar et al [22] investigated the effect of RSW parameters on surface morphology of AISI304 steel spot joints.…”
Section: Introductionmentioning
confidence: 99%